2012
DOI: 10.1097/ftd.0b013e318244a7fd
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics in Stable Kidney Transplant Recipients After Conversion From Twice-Daily to Once-daily Tacrolimus Formulations

Abstract: The results of this study provide evidence for safe conversion from Tacrolimus BID to QD with appropriate trough concentration monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 12 publications
7
34
0
1
Order By: Relevance
“…Two studies reported significantly less within-subject variation in exposure after conversion to MR tacrolimus but provided no actual numerical data [43,60]. Another study reported similar within-and betweensubject variability between Prograf Ò and Advagraf Ò formulations [31]. No study to date has looked at withinpatient variability in exposure to Envarsus Ò XR.…”
Section: Xrmentioning
confidence: 94%
See 1 more Smart Citation
“…Two studies reported significantly less within-subject variation in exposure after conversion to MR tacrolimus but provided no actual numerical data [43,60]. Another study reported similar within-and betweensubject variability between Prograf Ò and Advagraf Ò formulations [31]. No study to date has looked at withinpatient variability in exposure to Envarsus Ò XR.…”
Section: Xrmentioning
confidence: 94%
“…Three studies reported that within-subject variability [percentage coefficient of variation (% CV)] in AUC 0-24 or C min decreased significantly following conversion from Prograf Ò to Advagraf Ò [28,35,43], while two studies could find no significant difference [31,45]. Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35].…”
Section: Xrmentioning
confidence: 97%
“…The data regarding conversion from immediate release to prolonged release tacrolimus posttransplant are limited. Although some have found such conversion to be well tolerated and effective [19][20][21][22], others have expressed concern for increased risk of rejection in stable kidney transplant recipients [23]. One study showed that such a conversion may necessitate an increase in the daily dose of Astagraf/ Advagraf by approximately 30% to maintain the target blood trough level unchanged [24].…”
Section: Key Pointsmentioning
confidence: 94%
“…Међутим, показано је да 50% паци-јената након конверзије захтева промену дозе у смислу повећања или смањења оне која је иницијална након конверзије [25][26][27][28][29][30][31] . Због тога, тренутно су у току клиничке студије у којима је иницијална доза при конверзији 70% од дозе пре конверзије 32 .…”
Section: 25unclassified